STRATEGI PENINGKATAN KUALITAS KERAJINAN ANYAMAN PURUN UNTUK MENINGKATKAN PENDAPATAN EKONOMI RAKYAT DESA PEMATANG PANJANG - KALIMANTAN TENGAH - Hendra Afrianto (Jurnal Ilmiah Ekonomi, Manajemen dan Bisnis, 2020)
In the competitive arena of international trade, amplified by the industrial revolution 4.0 and its propagation of seemingly unbounded free trade, business entities are compelled to evolve strategies that influence consumer decisions favorably to thrive. This research investigates the strategic avenues to enhance the quality of purun woven crafts, aiming to augment the economic prosperity of Pematang Panjang Village, a community where this craft has been a tradition for over six decades yet has seen limited development. Utilizing a qualitative research method, primary data was gathered through direct interviews with local craftsmen, supplemented by secondary sources. The findings indicate that the current strategies to improve the craft's quality are underperforming against theoretical expectations. This research underscores the need for innovative approaches in the craft's production processes and market strategies to better harness the economic potential of the local industry, suggesting a pivotal shift towards more dynamic and market-responsive practices. This adjusted abstract encapsulates the research's originality, objectives, methods, results, and implications within the required word count.